EVALUASI PENERAPAN DESAIN INKLUSIF DAN BERKELANJUTAN PADA MUSEUM KOTA LAMA SEMARANG - Arnia Iga Meirta; Gagoek Hardiman; Siti Rukayah (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2023)
Abstract: Semarang Old Town Museum is one of the revitalization programs of Semarang Old City, which in its development plan realizes the 11th sustainable development goal of